PENILAIAN EFEKTIVITAS PADA MESIN DAICH DENGAN METODE OVERALL EQUIPMENT EFFECTIVENES (OEE) DI PT UB - Annisa Purbasari; Ahmad Salim (Universitas Riau Kepulauan, 2021)
PT. UB is a company in Indonesia engaged in the electronics manufacturing industry that produces IC products. The company seeks to improve the performance of its engines through improved production processes. One of the production machines that have high performance is the DAICHI machine in the cleaning process. However, the performance of a DAICHI machine can be hampered if it experiences downtime, damage or does not work effectively. This research aims to assess the effectiveness of DAICHI machines in the cleaning process with oee methods. The results of this study showed that the availability ratio value was 85.77%, performance efficiency was 65.45%, and the rate of quality was 99% with an OEE value of 54.49%, so the effectiveness of the machine had not met established standards or the machine did not work effectively. The availability ratio and performance efficiency factors that most cause the OEE value of DAICHI machines in the cleaning process do not meet the standards.